Intellectual Property Law in China and Pakistan: A Comparative Analysis of Computer Software Protection (International Journal of Scientific Research and Management (IJSRM), 2025)
Computer software protection presents complex and interrelated challenges, particularly in copyright and patent law. Developing countries in the Asia-Pacific region, including Pakistan, struggle with inadequate legal frameworks to safeguard both national and international software, exacerbated by the rapid evolution of software-related products and services. In contrast, China has made substantial progress in strengthening software protection through comprehensive copyright laws, regulatory measures, and inter-ministerial coordination frameworks that promote the use of legitimate software. These initiatives have significantly improved China’s software copyright protection system, fostering the growth of its software industry. Furthermore, China’s Patent Examination Guidelines provide a structured approach to software patentability, distinguishing between conventional software, which lacks patent protection, and innovative software, which qualifies for such protection. Given these advancements, Pakistan can benefit from implementing well-defined legal and administrative measures to enhance software protection. This study examines China’s current software protection policies, legislative and administrative frameworks, and their applicability to Pakistan, offering insights into potential legal reforms to strengthen software protection in the country.